Perianal necrotizing fasciitis: a case report and literature review - Li Jingjing; Xu Xinyi; Zeng Yusha; Xue Yahong (结直肠肛门外科)
Necrotizing fasciitis has a low clinical incidence, and surgical debridement combined with broad-spectrum antibiotics represents the primary treatment approach. Timely surgical debridement and drainage are crucial for saving patients’ lives, with anatomical exploration during debridement and drainage methods requiring guidance from both imaging and clinical assessments. Particularly when the lesion severely extends to the anterior abdominal wall, popliteal fossa, thighs, and other locations, thorough debridement and adequate drainage are vital measures to reduce mortality. This article reports the diagnosis and treatment process of a patient with perianal necrotizing fasciitis, aiming to share relevant clinical experiences with colleagues.